The Stability of Phycocyanin, Phycoerythrin, and Astaxanthin from Algae Towards Temperature, pH, Light, and Oxygen as a Commercial Natural Food Colorant - Goyudianto, Bryan Ashley; Meliana, Catarina; Muliani, Debby; J, Jeslin; Sadeli, Yohana Elma; Ratnasari, Nanda Rizqia Pradana (Indonesia International Institute for Life Sciences, 2021)
Nowadays, food industries are exploring more about naturally-derived colorants. Algae is proposed to be an excellent alternative source for natural colorants as it needs lesser biomass. Phycocyanin, phycoerythrin, and astaxanthin are commercially used blue-green, red, and red-orange algae-sourced pigments due to their high protein yield, health benefits, and ease of extractions methods. A literature survey conducted using Google Scholar and ScienceDirect database with inclusion and exclusion criteria gained 44 papers used as primary references to assess those algae pigments' stability towards temperature, pH, light, and oxygen for food applications. Low pH levels and addition of preservatives (sugar, citric acid) or polyhydric alcohols enhance phycocyanin range of stability (pH of 5–6 and >40oC with pH >5 or <3). Phycoerythrin’s stability at -20 to 4°C and neutral pH is improved by adding additives (citric acid, benzoic acid) or nanofibers, cross-linking method, complex formation, and microencapsulation. Phycocyanin and phycoerythrin’s light stability depend on the light’s composition, quality, and quantity; hence, utilization of dark-colored packaging to prevent light exposure is done. Astaxanthin’s instability towards light exposure (causing photoexcitation), temperature of >30°C, and pH of >4 can be solved through chitosan solution coating and microencapsulation using various wall materials and complex formation. Phycocyanin is unaffected against oxygen (unlike phycoerythrin and astaxanthin), yet all of them exert antioxidant properties. Therefore, the inconsistency of these colorants’ stability depending on food processing conditions demand further development through research to widen their commercial food applications.